DECOMPOSITION OF BOCR “ ARISAN MAJELIS TA’LIM”AS SUPPORT PROGRAM FOR MICRO SYARIAH FINANCIAL INSTITUTION, CASE STUDY OF BOGOR CITY - Fiqih Afriadi (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
The purpose of this research is to uncover the uniqueness of Beneffit, Opportunity, Cost and Risk (BOCR) from arisan majelis ta’lim in supporting the sustainability of Sharia Micro Financial Institution (SMFI). Benefit and Opportunity need to be known as the positive side of the arisan majelis ta’lim in SMFI, while the Cost and Risk needs to be known to see the negative side. To reveal the uniqueness of BOCR methodology is done byusing the methodology of ANP BOCR problem decomposition. Decomposition of the problem is done by surveying to arisan majelis ta’lim in Bogor city and also indepth interview to practitioners of arisan majelis ta’lim and SMFI practitioners. The result of the research shows several Benefits that can be obtained include; increase the number of members, high social capital honesty and integrity typical of “wong cilik” , and low cost. For Opportunity that can be obtained that is; savings fund opportunities, poor empowerment opportunities, microfinance opportunities, and opportunities for increased financing returns. The various costs that must be in the responsibility is; operational costs,empowerment costs, product development costs, and socialization and education costs. While some risks that need to be the attention that is; credit risk, sharia compliance risk, operational risk, and social risk.